Innovative Approaches to English Language Teaching in Indonesian Public Islamic Schools: Insights and Challenges - Saefurrohman; Balinas, Elvira S.; Rosadi, Abas; Nafisah, Shofia Lina; Pascarina, Hanifa (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background: In Indonesia's public Islamic secondary schools, English Language Policy and Planning (ELPP) faces challenges such as resource limitations, a lack of qualified educators, and a non-standardized curriculum. However, despite these challenges, compared to ASEAN peers like the Philippines, Indonesia's approach lacks focus on student-centered learning, underscoring the need for enhanced ELPP strategies. Methodology: Four English language teachers and one headmaster participated as respondents in this research to provide comprehensive data findings. Data were collected through interviews conducted over the course of one month, employing guided questions. Subsequently, descriptive analysis was utilized to analyze the data. Findings: English's mandatory integration in secondary education, especially in Madrasah Tsanawiyah, highlights its crucial academic role. Analyzing educational policies and curricular shifts, from competency-based to the Merdeka curriculum, showcases Indonesia's deliberate push for English proficiency. Interviews stress the Merdeka Curriculum's CEFR alignment, prioritizing student empowerment through learner-centered methods and technology. Despite efforts, challenges remain in public Islamic schools, with teachers advocating for supportive environments due to limited exposure and resources. Conclusion: The complex nature of these challenges necessitates the cooperation of politicians, educators, and administrators to establish an atmosphere that promotes successful English language acquisition while also honoring Indonesia's distinct cultural and linguistic diversity. Originality: This study uniquely explores ELPP in Indonesia's public Islamic secondary schools, highlighting the balance between English proficiency and cultural preservation, offering fresh insights into the ELPP discourse in a multicultural and multilingual context.